PERSEPSI MASYARAKAT TERHADAP TANAMAN SAYURAN HIDROPONIK PADA URBAN HYDROFARM DI KELURAHAN BATUKOTA KECAMATAN MALALAYANG KOTA MANADO - Meilania M.F Simbolon; Rine ., Kaunang; Mex Frans Lodwyk Sondakh (Sam Ratulangi University, 2021)
This research aims to determine the public's perception of hydroponic vegetable plants in Batukota Village, Malalayang District, Manado City. This research was carried out for 3 (three) months, from April to June 2021. This research was carried out in Batukota Village, Malalayang District, Manado City. The method of data collection is done by survey method, the data used are primary data and secondary data. Primary data were obtained from direct interviews with the people of Batukota Village using a questionnaire. Secondary data were obtained from the Urban Hydrofarm manager and the Batukota Urban Village Office, as well as other data deemed relevant. Analysis of the data used in this study is descriptive analysis with measurements using a Likert Scale. Sampling was carried out by means of Simple Random Sampling as many as 30 samples. The results showed that there were still many people in Batukota Village who did not know about vegetable crops using hydroponic techniques.